2012
DOI: 10.1093/nar/gks355
|View full text |Cite
|
Sign up to set email alerts
|

The Lin28 cold-shock domain remodels pre-let-7 microRNA

Abstract: The RNA-binding protein Lin28 regulates the processing of a developmentally important group of microRNAs, the let-7 family. Lin28 blocks the biogenesis of let-7 in embryonic stem cells and thereby prevents differentiation. It was shown that both RNA-binding domains (RBDs) of this protein, the cold-shock domain (CSD) and the zinc-knuckle domain (ZKD) are indispensable for pri- or pre-let-7 binding and blocking its maturation. Here, we systematically examined the nucleic acid-binding preferences of the Lin28 RBD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
113
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(130 citation statements)
references
References 68 publications
14
113
0
1
Order By: Relevance
“…Isolated studies with the ZnF domains also suggest that they partially unfold pre-let-7 targets (56). Additionally, a FRET study revealed that the CSD of Lin28 remodels the terminal loop of pre-let-7 by unwinding the upper stem region (37). We propose that the Lin28-mediated remodeling of RNA disrupts the G4 structure because in the presence of Lin28, the Lin28-binding RNAs no longer induce NMM fluorescence.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Isolated studies with the ZnF domains also suggest that they partially unfold pre-let-7 targets (56). Additionally, a FRET study revealed that the CSD of Lin28 remodels the terminal loop of pre-let-7 by unwinding the upper stem region (37). We propose that the Lin28-mediated remodeling of RNA disrupts the G4 structure because in the presence of Lin28, the Lin28-binding RNAs no longer induce NMM fluorescence.…”
Section: Discussionmentioning
confidence: 87%
“…Lin28 induces a conformational change in its RNA targets (32,36,37,56). We hypothesized that the Lin28-induced RNA rearrangement might remodel the RNA G4 structure.…”
Section: Lin28 Binding Disrupts the Ability Of Lin28 Rna Targets To Imentioning
confidence: 99%
See 2 more Smart Citations
“…A GGAGA motif was also reported to be present in 28% of the LIN28A-HiTS-CLIP defined mRNA-binding sites and was the most significantly enriched sequence element (Wilbert et al 2012). Co-crystals of mouse or Xenopus LIN28 proteins with fragments of Xenopus prelet-7f miRNA showed that both, CSD and ZKD, interacted with single-stranded regions within the pre-let-7 loop, corresponding to a pyrimidine-rich segment and a GGAG motif, respectively (Nam et al 2011;Mayr et al 2012). These interactions were similar to those previously observed for bacterial CSDs, which bound single-stranded pyrimidine-rich sequences with very few nucleobase-specific contacts (Phadtare and Inouye 1999; Max et al 2006).…”
Section: Introductionmentioning
confidence: 97%